2015
DOI: 10.1093/nar/gkv337
|View full text |Cite
|
Sign up to set email alerts
|

A novel family of integrases associated with prophages and genomic islands integrated within the tRNA-dihydrouridine synthase A (dusA) gene

Abstract: Genomic islands play a key role in prokaryotic genome plasticity. Genomic islands integrate into chromosomal loci such as transfer RNA genes and protein coding genes, whilst retaining various cargo genes that potentially bestow novel functions on the host organism. A gene encoding a putative integrase was identified at a single site within the 5′ end of the dusA gene in the genomes of over 200 bacteria. This integrase was discovered to be a component of numerous genomic islands, which appear to share a target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 88 publications
11
47
0
Order By: Relevance
“…This finding is consistent with other that have reported A. baumannii strain AYE and ATCC17978-harbored copper tolerance genes on G08 and G62, respectively [13,15]. Similar to other prophages and genomic islands that have been reported in A. baumannii [35], G08 detected in AB003 was integrated within the tRNA-dihydrouridine synthase A (dusA) gene. Here, our bioinformatics analysis also found that G08 and untypeable GEIs carried cluster C were detected on conjugative plasmids of various Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with other that have reported A. baumannii strain AYE and ATCC17978-harbored copper tolerance genes on G08 and G62, respectively [13,15]. Similar to other prophages and genomic islands that have been reported in A. baumannii [35], G08 detected in AB003 was integrated within the tRNA-dihydrouridine synthase A (dusA) gene. Here, our bioinformatics analysis also found that G08 and untypeable GEIs carried cluster C were detected on conjugative plasmids of various Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 91%
“…3h), which has been previously reported in A. baumannii strain LAC-4 [63]. In addition to strain ATCC 17978, strains AB0057 and AB6870155 also encode part of this island, which has inserted into the dusA locus [64]. Furthermore, genes orthologous to the CDF family system encoded by A1S_2929 in the ATCC 17978 Cu-resistance island are also found in AB0057, AB6870155, ATCC 19606T and ACICU, but at different loci (Fig.…”
Section: Resultssupporting
confidence: 61%
“…100 bp into the coding sequence of dusA , which encodes tRNA-dihydroxyuridine synthase A. A recent study [67] revealed that known integrase genes, at least half of which belong to prophages, were found adjacent to the host dusA gene in over 200 bacterial species. Furthermore, a 21 base pair motif found at the prophage-host DNA junctions in many bacteria was present at the prophage junctions, attL and attR , of C. rodentium (Φ stx 2dact ) and C. rodentium (ΦΔ stx 2dact ::kan R ), as well as at the presumed attB phage insertion site in the parental C. rodentium dusA gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bent arrows indicate direction of transcription of Q, stx , and phage late genes. Depicted are attL and attR sequence motifs, characteristic of other prophages inserted within the host dusA gene ([67]). Within this sequence, a bolded seven-base “core” sequence, perfectly conserved in attL and attR , as well as in the Φ stx 2dact attP sequence and the parental attB sequence in C. rodentium dusA (not shown), is the cross-over site for phage integration and excision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation